Dormant, tallgrass-prairie forage: influence of ruminal degradable protein on intake by beef cows and fermentation characteristics - H.H. Koster; R.C. Cochran; E.S. Vanzant; G. St Jean; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1994)
Five ruminally and duodenally fistulated Angus x Hereford cows were fed dormant tallgrass-prairie forage ad libitum to monitor intake and fermentation responses associated with providing increasing amounts of supplemental ruminal degradable protein (RDP). The RDP was provided from sodium caseinate and infused intraruminally immediately before feeding forage. Levels of RDP were 0, 180, 360, 540, and 720 g/d. Maximal intake of dormant, tallgrass-prairie forage occurred with provision of 540 g RDP/d. Ruminal dry matter fill declined with increasing level of RDP infusion. Increasing supplmentation of RDP generally improved ruminal fermentation characteristics.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Beef cows; Ruminal degradable protein; Intake; Forage